Pelestarian Ludruk Melalui Pembelajaran Menulis Cerita Fantasi Kelas VII SMP Bina Bangsa 2 Surabaya - Bagaskoro Angkasa, Muhammad Bagus; Sujinah (Universitas Insan Budi Utomo, 2026)
This study aims to describe the challenges of preserving ludruk as a traditional art form and to examine the improvement of fantasy story writing skills based on ludruk values among seventh-grade students at SMP Bina Bangsa 2 Surabaya. This research employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with teachers and students, and document analysis of students’ fantasy story texts. The findings reveal that, at the initial stage, most students had limited knowledge of ludruk, which resulted in weak story structure, underdeveloped imagination, and inaccurate language use in their writing. After the implementation of fantasy writing instruction integrated with ludruk through text modeling, scaffolding, and the use of digital media, significant improvements were observed. Students’ texts demonstrated more complete narrative structures, including orientation, complication, resolution, and reorientation, more creative imaginative elements, and more accurate language use. Furthermore, the integration of local culture increased students’ learning motivation, active participation, and appreciation of traditional arts. This study concludes that ludruk-based fantasy writing instruction is effective in enhancing students’ creative literacy while simultaneously supporting the contextual and sustainable preservation of local culture.